(untitled) (Research, Society and Development, 2022)
This paper is part of a Master dissertation in Education that is about the “Tiradentes” Military Police State School. It has as aim to unveil why the school has had several denomination changes in a short period of time, i.e., from 1986 to 2000. As it is a research in the field of history of education, the optics turned to the history of school institutions, having as theoretical framework the work of Paulo Nosela and Ester Buffa (2013). To do so, laws and school documents were used, provided by the school, by the Military Police, by the Military Fire Department, as well as by the former students. After the analysis, it was perceived that the changes, which occurred in the name of the teaching unit, were basically a result of the demands and referrals due to the political context of the time that directly influenced the educational law.